السلوك التنظيمي وإدارة المؤسسات الرياضية - شنوف, خالد; عدة, بن علي; حساني, مسعود (https://www.asjp.cerist.dz, 2018)
Organizational behavior is a fundamental pillar for the success of any institution gym, this depends on the extent of understanding of the institution and these behaviors and forecasting and control and develop the scientific basis, this study comes a conceptual approach to the subject of organizational behavior by highlighting the importance and objectives of: identifying the causes of behavior and forecasting the behavior in the case of identifying the causes and direction and control in the conduct of the causes, and its components, and theories, and address to what sports institutions, types, and objectives... The importance of administrative activity in the institution of sports, depending on the descriptive approach to Analytical.
Keywords: السلوك التنظيمي، إدارة المؤسسات الرياضية